Pemanfaatan Teknologi Artificial Intelligence (AI) dalam Media Pembelajaran IPA untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SD - Nirmala Amelia; Maulida Nur Khasanah; Nurul Hidayah; Hanifatun Nizzah; Ghaida Indra; Zulherman Zulherman (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research discusses the impact of using Artificial Intelligence (AI) in science learning at school. The low critical thinking skills of students can be proven by the passivity of students during the learning process, where students are more often just listeners to the material delivered by the teacher. This happens because of the monotonous methods and models used by teachers, and only continue to rely on Teacher Centered Learning. So that it can affect learning outcomes and students' critical thinking skills. This research uses a qualitative method with a literature study, which shows that the application of AI can visualize abstract learning material, thus making the teaching and learning process more interesting and effective. In addition, the importance of teachers' role in integrating AI technology into learning is also emphasized, where teachers need to improve their knowledge of AI-based digital technology to achieve better learning objectives. The research also notes that while the positive impacts of AI are predominant, there is a need to anticipate the negative impacts that may arise from its use in education. This is so that advancements in the education sector can take place more efficiently, effectively and safely. The conclusion of this study is that the use of AI-based technology can improve students' critical thinking skills as well as provide alternative interactive learning media in science subjects in elementary schools.